The Effectiveness of Blended Learning Combined the Team Game Tournament on the Learning Outcomes of Electrical Engineering Students - Arga, Hardhika Nur; Nugraha, Ariadie Chandra; Sudira, Putu; Daryono, Rihab Wit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The pandemic condition forced schools to carry out online learning.As a result, learning becomes ineffective. This study aims to determine the effectiveness of the learning model and the differences in learning outcomes in the subject of Basic Electromechanical Work using the blended learning model of the flipped classroom combined with the team game tournament with the lecture learning model. This study uses a quasi-experiment approach. The research subjects were 68 students of class X Electrical Engineering. The research design used a non-equivalent control group design. Data analysis used description analysis, prerequisite test, and hypothesis. Hypothesis testing using the Mann-Whitney and Wilcoxon tests. The results showed that the flipped classroom learning model was more effective than the lecture model, indicated by an increase in the pretest-posttest score of 3.74 and the control class of 2.24. The flipped classroom model has a significant difference in learning outcomes compared to the lecture model. For students, the use of flipped classroom learning makes it easier and increases interest in learning so that they become more creative and critical which has an impact on increasing students' cognitive, affective and psychomotor abilities. The application of the team game tournament as a learning medium is able to attract students' interest in the learning process.